The Construction of Customary Judge's Decision on Plantation Conflict Resolution from the Perspective of Huma Betang Philosophy: A Case Study in Seruyan Regency, Central Kalimantan: - - Achmadi Achmadi; Armadiansyah Armadiansyah; Sanawiah Sanawiah; Muhammad Wahdini; Turdialiev Mukhammad Ali Polatjon Ogli (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of the study: This study examines the construction of the decision of the Basara Hai Customary Peace Assembly No. B./01/T.9.DKA.-KTG/IV/2024 which has implications for the decision of the Palangka Raya District Court Number 55/Pid.B/2024/PN Plk to resolve the plantation conflict that occurred in Seruyan Regency, Central Kalimantan Province, Indonesia which had the potential to provide a lighter sentence for the defendant. Methodology: The study utilized a mixed research method consisting of doctrinal (normative) and non-doctrinal (socio-legal) research methods. Both methods were used to analyze legislative products or court decisions at the macro-analysis level empirical realities. They aimed to study and solve problems that were conceptualized at the micro-analysis level as symbolic realities. This study used the sociological and anthropological juridical approach methods that aimed to observe written laws and the law in practice. Results: The findings of this study showed that the construction of customary judges' decisions upholds the values ​​of belom bahadat (customs of life regarding politeness/ethics/high morals of the Dayak indigenous community). These values ​​must be applied in all philosophical, sociological, and legal aspects. The decision of the customary judge also has implications for the construction of the Palangka Raya Court Decision No. 55/Pid.B/2024/PN that aims to provide legal justice and certainty for the disputing parties. Applications of this study: This study offers findings from the construction of customary judges in upholding customary law based on the values ​​of belom bahadat which have implications for the Palangka Raya Court Decision No. 55/Pid.B/2024/PN in providing justice for defendants who have undergone customary trials and the defendant's obedience to applicable customary laws as an effort to resolve conflicts. Novelty/Originality of this study: The doctrine of customary law in the form of a customary judge's decision from the Huma Betang perspective is used by state judicial institutions as the basis in providing recommendations or legal considerations for law enforcement in providing justice and legal certainty for the disputing parties. Keywords: Decision construction, Customary Judge, Philosophy, Huma Betang.   ABSTRAK  Tujuan penelitian: Penelitian ini mengkaji konstruksi putusan Majelis Perdamaian Adat Basara Hai Nomor B./01/T.9.DKA.-KTG/IV/2024 yang berimplikasi pada putusan Pengadilan Negeri Palangka Raya Nomor 55/Pid.B/2024/PN Plk untuk menyelesaikan konflik perkebunan yang terjadi di Kabupaten Seruyan, Provinsi Kalimantan Tengah, Indonesia yang berpotensi memberikan hukuman yang lebih ringan bagi terdakwa. Metodologi: Penelitian ini menggunakan metode penelitian campuran yang terdiri dari metode penelitian doktrinal (normatif) dan non-doktrinal (sosio-legal). Kedua metode tersebut digunakan untuk menganalisis produk perundang-undangan atau putusan pengadilan pada level analisis makro realitas empiris. Tujuannya adalah untuk mengkaji dan memecahkan permasalahan yang dikonseptualisasikan pada level analisis mikro sebagai realitas simbolik. Penelitian ini menggunakan metode pendekatan yuridis sosiologis dan antropologis yang bertujuan untuk mengamati hukum tertulis dan hukum dalam praktik. Hasil: Hasil penelitian ini menunjukkan bahwa konstruksi putusan hakim adat menjunjung tinggi nilai-nilai belom bahadat (adat istiadat kehidupan mengenai kesopanan/etika/moral yang tinggi dari masyarakat adat Dayak). Nilai-nilai tersebut harus diterapkan dalam segala aspek filosofis, sosiologis, dan hukum. Putusan hakim adat tersebut juga berimplikasi pada konstruksi Putusan Pengadilan Palangka Raya Nomor 55/Pid.B/2024/PN yang bertujuan untuk memberikan keadilan dan kepastian hukum bagi para pihak yang bersengketa. Aplikasi penelitian ini: Penelitian ini menawarkan temuan dari konstruksi hakim adat dalam menegakkan hukum adat berdasarkan nilai-nilai belom bahadat yang berimplikasi pada Putusan Pengadilan Palangka Raya Nomor 55/Pid.B/2024/PN dalam memberikan keadilan bagi terdakwa yang telah menjalani persidangan adat dan ketaatan terdakwa terhadap hukum adat yang berlaku sebagai upaya penyelesaian konflik. Kebaruan/Keaslian penelitian ini: Doktrin hukum adat berupa putusan hakim adat dari perspektif Huma Betang digunakan oleh lembaga peradilan negara sebagai dasar dalam memberikan rekomendasi atau pertimbangan hukum bagi penegak hukum dalam memberikan keadilan dan kepastian hukum bagi para pihak yang bersengketa. Kata Kunci: Konstruksi putusan, Hakim Adat, Filsafat, Huma Betang.